3D-Printed Bubble-Free Perfusion Cartridge System for Live-Cell Imaging - Daigo Terutsuki; Hidefumi Mitsuno; Ryohei Kanzaki (Sensors, 2020)
The advent of 3D-printing technologies has had a significant effect on the development of medical and biological devices. Perfusion chambers are widely used for live-cell imaging in cell biology research; however, air-bubble invasion is a pervasive problem in perfusion systems. Although 3D printing allows the rapid fabrication of millifluidic and microfluidic devices with high resolution, little has been reported on 3D-printed fluidic devices with bubble trapping systems. Herein, we present a 3D-printed millifluidic cartridge system with bent and flat tapered flow channels for preventing air-bubble invasion, irrespective of bubble volume and without the need for additional bubble-removing devices. This system realizes bubble-free perfusion with a user-friendly interface and no-time-penalty manufacturing processes. We demonstrated the bubble removal capability of the cartridge by continually introducing air bubbles with different volumes during the calcium imaging of Sf21 cells expressing insect odorant receptors. Calcium imaging was conducted using a low-magnification objective lens to show the versatility of the cartridge for wide-area observation. We verified that the cartridge could be used as a chemical reaction chamber by conducting protein staining experiments. Our cartridge system is advantageous for a wide range of cell-based bioassays and bioanalytical studies, and can be easily integrated into portable biosensors.